2019
DOI: 10.1039/c9ra05709a
|View full text |Cite
|
Sign up to set email alerts
|

Visual detection of Fusarium proliferatum based on asymmetric recombinase polymerase amplification and hemin/G-quadruplex DNAzyme

Abstract: Asymmetric recombinase polymerase amplification and hemin/G-quadruplex DNAzyme-based visual detection of F. proliferatum is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Other strategies, including primer exchange [45] and rolling circle amplification [46], require a deep understanding of the assay, accompanied by complicated primer design. We also explored the strategy of asymmetric RPA (aRPA) [47] to generate ssDNA for cas12a activation. While the strategy has some success in producing high fluorescence signal compared to normal RPA reaction for cas12a PAM-less activation, we found that the result between different templates might not be consistent, and aRPA generated an unspecific amplification with the genomic template possibly due to a high concentration of primer, rendering the detection method less reliable (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies, including primer exchange [45] and rolling circle amplification [46], require a deep understanding of the assay, accompanied by complicated primer design. We also explored the strategy of asymmetric RPA (aRPA) [47] to generate ssDNA for cas12a activation. While the strategy has some success in producing high fluorescence signal compared to normal RPA reaction for cas12a PAM-less activation, we found that the result between different templates might not be consistent, and aRPA generated an unspecific amplification with the genomic template possibly due to a high concentration of primer, rendering the detection method less reliable (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…16) and adenosine 5 0 -triphosphate, 17 micro-RNA, 18 protein biomarkers like thrombin, 19 cancer cells, 20 and bacteria such as Escherichia coli 21 and Fusarium proliferatum. 22 Nevertheless, most of these measurements may suffer from the requirements of expensive yet bulky analytical instruments that can only be operated by well-trained personnel to obtain nal results, which make these useful biosensors difficult to be accessed in less-industrialized areas, in eld-based analysis, in emergency situations, or in-home healthcare services. The reports of emerging paper microuidics are a positive step towards developing promising alternative analytical devices for use in such resource-limited environments because of its many attractive properties.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Rolling circle amplication (RCA) is one of the most popular tools for signal amplication, which has been widely used for detection of miRNA, single nucleotide polymorphisms, pathogens, cancer cells and their biomarkers. [23][24][25] However, if there are two or more probes in the system, high background noise cannot be avoided, 26 which lowers the reliability of the results. For decreasing the background noise, 3 0ends of non-RCA related probes are always closed by spacers using many strategies related to RCA.…”
mentioning
confidence: 99%
“…The strategy is simple and cost effective, and it is not very sensitive. 25 Though the RPA-RCA-assisted assay has more steps, each reaction could be performed at room temperature or 37 C. The signicant advantage of our strategy is low background. T5 exonuclease digests all linear DNA, and only single stranded circle DNA and probe 2 are in nal solution.…”
mentioning
confidence: 99%